On the Problem of Dominants and Determinants of Social Development - Pogosyan, Vardges (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
On the basis of a correct methodological implications the author makes a conclusion that the amplitude of the social development due to the invariant social structure, based on institutional matrix and the immanent mode of production, and that structural changes can be the only intrasystem which actualizes the question of the necessity of certain restrictions in the modernization practice.
Keywords: determinism, the dominants, socio-cultural component, institutional matrix, modernization, invariance, the Asian mode of production